Sofosbuvir as treatment against dengue? - Gan, Chye Sheng; Lim, See Khai; Chee, Chin Fei; Yusof, Rohana; Heh, Choon Han (Wiley, 2017)
Dengvaxia® (CTD-TDV), the only licensed tetravalent dengue vaccine by Sanofi Pasteur, was made available since 2015. However, administration of CTD-TDV, in general, has not received the prequalification recommendation from the World Health Organization. Having a universal antidengue agent for treatment will therefore beneficial. Accordingly, the development of nucleoside inhibitors specific to dengue viral polymerase that perturb dengue infection has been studied by many. Alternatively, we have used a marketed anti-HCV prodrug sofosbuvir to study its in silico and in vitro effects against dengue. As a result, the active metabolite of sofosbuvir (GS-461203) was predicted to bind to the catalytic motif (Gly-Asp-Asp) of dengue viral polymerase with binding affinity of −6.9 kcal/mol. Furthermore, sofosbuvir demonstrated excellent in vitro viral inhibition with an EC90 of 0.4 μm. In addition, this study demonstrated the requirement of specific liver enzymes to activate the prodrug into GS-461203 to exert its antidengue potential. All in all, sofosbuvir should be subjected to in-depth studies to provide information of its efficacy toward dengue and its lead potential as DENV polymerase inhibitor in human subjects. In conclusion, we have expended the potential of the clinically available drug sofosbuvir as treatment for dengue.